Дослідження Виповзівського археологічного комплексу 2009 р. - Скороход, В.М. (Археологічні дослідження в Україні, 2010)
Archaeological research was carried out on the territory of the archaeological complex near village Vypovziv in Kozelets Region in Chernihiv Oblast, in the lower reaches of the Desna River (site of the settlement, trading quarter, and downtown) which is ruining because of weathering. Four half-dugout dwellings of the 9th and 10th c. were discovered after the excavation; limits of the expansion of the cultural level at the trading quarter and in downtown were broadened.